1997
DOI: 10.1016/s0168-9002(97)00632-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of trapping and detrapping in semi-insulating GaAs detectors

Abstract: To investigate the trapping and detrapping in SI-GaAs particle detectors we analyzed the signals caused by 5.48 MeV alpha particles with a charge sensitive preamplifier. From the bias and temperature dependence of these signals we determine the activation energies of two electron traps. Additional simulation and measurements of the lifetime as a function of resistivity have shown that the EL2 + is the dominant electron trap in semi-insulating GaAs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Compared to the widely used Si and Ge detectors, both of which are limited to either room or liquid nitrogen cooled temperatures, respectively, GaN is characterized by a much wider band-gap, making it capable of working in environments well above room temperature. Shortcomings in other wide band-gap semiconductors such as short carrier lifetimes (10 ns) in GaAs due to the dominant EL2 native deep-level defect, 30 the large number of deep-level defects 31 in AlN, and the high cost of diamond 32 limits their implementation as radiation detectors. Compared to SiC that has an in-direct band-gap, GaN has a higher mobility and thus better electrical properties.…”
Section: A Basic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the widely used Si and Ge detectors, both of which are limited to either room or liquid nitrogen cooled temperatures, respectively, GaN is characterized by a much wider band-gap, making it capable of working in environments well above room temperature. Shortcomings in other wide band-gap semiconductors such as short carrier lifetimes (10 ns) in GaAs due to the dominant EL2 native deep-level defect, 30 the large number of deep-level defects 31 in AlN, and the high cost of diamond 32 limits their implementation as radiation detectors. Compared to SiC that has an in-direct band-gap, GaN has a higher mobility and thus better electrical properties.…”
Section: A Basic Parametersmentioning
confidence: 99%
“…Undoped GaN shows n-type properties due to the residual shallow donors such as oxygen in MOCVD-grown GaN 13 and silicon in HVPE-grown GaN 67 (shallow donors are defined as impurities that ionize at room temperature, which corresponds to an activation energy of 100 meV). Oxygen donors result in a background free-carrier concentration between 10 15 and 10 17 cm À3 with an activation energy of [30][31][32][33] that is below the conduction band minimum (CBM). GaN can be intentionally doped with Si to form an n-type material through either as-growth or post-growth implantation.…”
Section: B Gan Growthmentioning
confidence: 99%
“…For a single electron-hole pair produced at a point with coordinate ı 0 , the CCE is written where d is the electrode spacing (detector thickness) and λ e and λ h are the electron and hole drift lengths, respectively [15]. The drift lengths are given by λ e = µ e τ e E,…”
Section: Figures Of Meritmentioning
confidence: 99%
“…Carrier trapping, particularly in high fields (10 4 V cm -1 ), is mainly by the EL2 level (0.8 eV) [2,10,15,19]. Its capture cross section grows to about 8 × 10 −14 cm 2 with field strength.…”
Section: Selection Of a Sensing Materialsmentioning
confidence: 99%
“…It has been shown that these deep donors could limit the lifetime of charge carriers by acting as trapping centres [6]. Electron-hole pairs generated by incoming X-ray photons can be trapped on their way to the readout electrodes, so that only a fraction of the generated charge is detected.…”
Section: Imaging Propertiesmentioning
confidence: 99%